Density-functional based tight-binding for the study of CO2/MOF interactions: the case of Zn(ADC)·DMSO. Issue 5 (13th April 2017) - Li, Jie; Foster, Michael E.; Sohlberg, Karl
Abstract: The adsorption of CO2 on the metal–organic framework, Zn(ADC) · DMSO, is studied using density functional-based tight-binding calculations with empirical dispersion correction (DFTB-D). Validation calculations predict bulk structure parameters that are consistent with published X-ray structure data for the material. The method is further validated by showing that DFTB-D predicts surface structures and CO2 binding energies in good agreement with the results of DFT/PW91-D calculations for both Zn(ADC) · DMSO and Cu(BTC) · 3H2 O. A corrugated 1 0 0 surface of Zn(ADC) · DMSO is proposed that avoids cleaving through any aromatic rings to form the slab when studying the surface adsorption of CO2 . DFTB-D calculations of CO2 /surface interactions are combined with an enhanced Langmuir-type adsorption model to investigate the adsorption efficiency of CO2 on the Zn(ADC) · DMSO surface. The dependence of this adsorption on particle size and shape, and its sensitivity to errors in the predicted binding energy on the order of the anticipated accuracy of the calculated binding energies are discussed. By comparison to DFT/PW91-D calculations, we conclude that DFTB-D is a cost-effective and reliable tool to predict adsorption behaviour for MOFs of this type. Finally, it is found that for this newly synthesised Zn · ADC MOF to attain a specific CO2 adsorption capacity comparable to that of conventional porous MOFs, its particle size must be decreased to the nanometer level.